Duchenne Muscular Dystrophy With Low Acidic α-Glucosidase Activity: Two Case Reports and Literature Review - He, Xiufang; Li, Xuandi; Lin, Yuese; Ba, Hongjun; Peng, Huimin; Zhang, Lili; Zhu, Ling; Qin, Youzhen; Li, Shujuan (Frontiers in Pediatrics, 2022)
Background: Pompe disease is usually considered in children with elevated creatine kinase (CK) level and decreased acidic α-glucosidase (GAA) enzyme activity. However, there are exceptions such as GAA pseudodeficiency alleles which result in lower GAA enzyme activity, but not cause Pompe disease. Here, we report two cases presenting with high CK level and low GAA activity who were ultimately diagnosed with Duchenne muscular dystrophy (DMD). Case presentation: Case 1 was a 2-month-old boy who presented with an extremely high serum CK level (5480~11880U/L) and low GAA activity (2.72nmol/1h/mg). The whole exome sequencing did not find the pathogenic GAA gene mutation, however, there was a DMD gene hemizygous variation (c. 7657C>T, p. Arg2553Ter) inherited from his mother, which was verified by the first-generation sequencing. Further genetic analysis of GAA identified two homozygous pseudodeficiency alleles (c.1726G>A, p. Gly576Ser and c.2065G>A, p. Glu689Lys), which were believed to induce the patient’s low GAA activity. Therefore, the boy was diagnosed with DMD although he had extremely low GAA activity. Case 2 was also a 2-month-old boy presenting with significant increase in CK level (12408~24828U/L). His blood GAA activity (colorimetric method) was 9.02nmol/1h/mg. Similarly, his whole exome sequencing did not find the pathogenic mutation of GAA gene but a DMD gene hemizygous variation (c.5571del, p. Lys1857AsnfsTer8), so he was diagnosed with DMD as well. Regarding GAA activity, case 2 was not as low as case 1, that was because his two GAA pseudodeficiency alleles were heterozygous. Conclusions: Pompe disease is usually screened in infants with high CK levels. We should be aware that pseudodeficiency alleles can cause low GAA activities but no Pompe disease. Genetic tests would be helpful to distinguish cases with GAA pseudodeficiency alleles from patients with some muscular disorder diseases such as DMD.